Effect of the COVID-19 pandemic on antibiotic consumption: A systematic review comparing 2019 and 2020 data - Fukushige, Mizuho; Ngo, Nhat-Hoang; Lukmanto, Donny; Fukuda, Shinichi; Ohneda, Osamu (Frontiers in Public Health, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic has influenced antibiotic consumption over a long period, with variability in trends among studies. We conducted this systematic review to explore and compare the effect of the pandemic on overall and individual antibiotic consumption in 2020 with that in 2019. Methods This systematic literature review was conducted using PubMed, EMBASE, and Web of Science databases. Data on antibiotic consumption in Japan was sourced from the Japan Surveillance of Antimicrobial Consumption. Results A total of 1,442 articles and reports were screened, and 16 eligible articles were reviewed. The included studies were conducted in Jordan, Australia, Canada, UK, Japan, Brazil, India, China, and the EU. There was no study from African and Southeast Asian Countries. Overall, antibiotic consumption in the community consistently reduced in 2020. Studies from Australia, Canada, Portugal, Spain, the UK, Japan, and the European Union reported both decreases in overall and selected individual antibiotics consumption. In contrast, hospital-based studies reported both increases and decreases. Hospital-based studies in Lebanon, Spain, Italy, India, and the UK reported an increase in antibiotic consumption in 2020. Studies reporting an interruption of antibiotic stewardship programs during the pandemic also reported increases in antibiotic consumption for hospitalized patients in 2020 compared with that in 2019. Conclusion Our results showed a different trend between communities and hospitals in antibiotic consumption during 2020 compared to 2019. The continuity of the antibiotic stewardship program might have influenced the antibiotic consumption trend variability among hospitals in 2020. Alongside this, the lack of information on antibiotic consumption from low-income countries and limited reports from middle-income countries revealed gaps that need to be urgently filled.